Chronic companions: An updated national cross-sectional study of metabolic syndrome comorbidities in outpatient visits for hidradenitis suppurativa - Elaine J. Ma; Alyssa M. Roberts; Peichi Chou; Abigail Katz; Charlotte Y. Jeong; Yvonne Nong; Maria T. Ochoa; April W. Armstrong (PLoS ONE, 2025)
Hidradenitis suppurativa (HS) is a painful, chronic inflammatory skin disease associated with significant physical and psychosocial burden. Increasing evidence suggests HS is linked to systemic metabolic dysfunction, including components of metabolic syndrome such as obesity, hypertension, and hyperlipidemia. This study aimed to assess the prevalence of metabolic comorbidities in patients with HS using data from the National Ambulatory Medical Care Survey (NAMCS), a nationally representative dataset of U.S. outpatient visits from 2014 to 2019. We conducted a cross-sectional analysis comparing HS-related visits to age- and sex-matched non-HS visits, using multivariate logistic regression adjusted for demographic and clinical covariates. Among 1.8 million weighted HS-related visits, the most prevalent metabolic comorbidities were hypertension (15.7%), obesity (8.6%), and hyperlipidemia (7.4%). Compared to non-HS controls, HS visits had significantly higher odds of hypertension (adjusted odds ratio [aOR] 2.90; 95% confidence interval [CI]: 2.88–2.92), obesity (aOR 3.12; 3.10–3.15), and hyperlipidemia (aOR 1.76, 1.74–1.77). No significant association was found between HS and type 2 diabetes mellitus (T2DM) or cerebrovascular disease. Mechanistically, chronic systemic inflammation in HS, driven by elevated cytokines such as TNF-α, IL-6, and IL-17, may contribute to endothelial dysfunction and metabolic dysregulation. Obesity, which is commonly associated with HS, exacerbates the inflammatory state and promotes follicular occlusion, while hyperlipidemia may amplify inflammation through oxidative stress and impaired immune resolution. These findings underscore the importance of recognizing metabolic risk factors in patients with HS, particularly within the context of outpatient settings where early intervention is feasible. Early identification and management of these comorbidities may improve long-term health outcomes. Further longitudinal studies are warranted to clarify causal relationships and support the development of multidisciplinary screening and care strategies for this high-risk population.